An ethnographic study of cultural values in the wedding rituals of the Samin Community, Blora - Ferra Nzulaika; Maria Krisnawati (Universitas Muhammadiyah Malang, 2025)
The Samin Tribe's traditional wedding customs are cultural practices passed down through generation, carried out with simplicity and a strong emphasis on philosophical values. This procession is far from the luxury of modern weddings, reflects philosophical values of loyalty, honesty, and social harmony. This study comprehensively describes the values embodied in the traditional wedding customs of the Samin people in Sambongrejo Village, Blora Regency. A qualitative descriptive approach was applied in this study. The collection data techniques used including direct observation of the wedding procession, interviews with customary leaders, and documentation of the related cultural activities. The research gap lies in the limited number of studies examining the Samin people's wedding procession both structurally and symbolically, especially in the context of the ethical values embodied in it and how these values are realised in the community's social actions. Most previous major studies have only highlighted the socio-political aspects or the history of Saminism resistance, while the cultural aspects of marriage remain limited. Most previous studies only highlight the socio-political aspects or the history of the Samin resistance movement, while the cultural aspects of marriage have received limited attention. The results of the study indicate that this customs consists of several main stages, namely: Nembung, Mbalesi Gunem, Ngendek, Ngawulo or Nyuwito, and Paseksen. Each stage has a symbolic function, such as Nembung, which reflects initial politeness and openness, and Paseksen, which is a manifestation of social legitimacy of the marriage bond. In addition, the Samin people adhere to their cultural values. One of their most important beliefs is that marriage can take place only once in a lifetime. The Samin people do not practice polygamy or polyandry because they follow the principle of Siji Kanggo Selawase (one for eternity). They believe that loyalty, simplicity, and honesty are the most important factors for harmony. Tradisi pernikahan tradisional Suku Samin merupakan praktik budaya yang diwariskan dari generasi ke generasi, dilaksanakan dengan kesederhanaan dan penekanan yang kuat pada nilai-nilai filosofis. Prosesi ini jauh dari kemewahan pernikahan modern, mencerminkan nilai-nilai filosofis kesetiaan, kejujuran, dan harmoni sosial. Studi ini secara komprehensif menggambarkan nilai-nilai yang terkandung dalam tradisi pernikahan tradisional Suku Samin di Desa Sambongrejo, Kabupaten Blora. Pendekatan deskriptif kualitatif diterapkan dalam studi ini. Teknik pengumpulan data yang digunakan meliputi pengamatan langsung terhadap prosesi pernikahan, wawancara dengan pemimpin adat, dan pendokumentasian aktivitas budaya terkait. Kesenjangan penelitian terletak pada minimnya kajian yang meneliti prosesi pernikahan masyarakat Samin secara struktural dan simbolik, khususnya dalam konteks nilai-nilai etis yang melekat di dalamnya serta bagaimana nilai-nilai tersebut diwujudkan dalam tindakan sosial masyarakat. Sebagian besar penelitian terdahulu hanya menyoroti aspek sosial-politik atau sejarah perlawanan Saminisme, sementara aspek budaya dalam konteks pernikahan masih sangat terbatas mendapat perhatian. Hasil penelitian menunjukkan bahwa tradisi ini terdiri atas beberapa tahapan utama, yaitu: Nembung, Mbalesi Gunem, Ngendek, Ngawulo atau Nyuwito, dan Paseksen. Setiap tahap memiliki fungsi simbolik tersendiri, seperti Nembung yang mencerminkan kesopanan dan keterbukaan awal, serta Paseksen yang merupakan perwujudan legitimasi sosial atas ikatan pernikahan. Selain itu, masyarakat Samin berpegang teguh pada nilai-nilai budayanya. Salah satu keyakinan terpenting mereka adalah bahwa pernikahan hanya dapat terjadi sekali seumur hidup. Masyarakat Samin tidak mempraktikkan poligami maupun poliandri karena mereka memegang teguh prinsip